THE INFLUENCE OF THE MAGNET SHAFT OF CURRENT TRANSFORMER AND SWITCHING TRANSISTORS ON THE POWER FACTOR OF THE STATIC SEMICONDUCTOR CONVERTERS OF UNIFORM STANDS FOR TESTING ELECTRIC TRACTION MOTORS - Loza, P. O. (Science and Transport Progress, 2008)
With the aim to develop the recommendations for increasing the capacity factor of static converters for the traction electric machines’ test stand this research has been carried out.